2010
DOI: 10.1510/icvts.2010.237883
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and mortality associated with deep sternal wound infections following coronary bypass surgery with or without concomitant procedures in a UK population: a basis for a new risk model?

Abstract: Deep sternal wound infection (DSWI) is a rare but serious complication following coronary artery bypass surgery. Our study investigates the risk factors and mortality associated with DSWI with other risk models for DSWI. Data was collected prospectively on 7602 patients undergoing coronary artery bypass grafting±concomitant surgery between April 1999 and September 2009 including DSWI. All 13 Society for Thoracic Surgeons (STS) risk scoring variables were assessed using logistic regression in relation to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
3
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 16 publications
2
42
3
6
Order By: Relevance
“…The higher rate of SWI found in the current study may be due to the post-discharge notification, which was different from what has been published in scientific journals [12,17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The higher rate of SWI found in the current study may be due to the post-discharge notification, which was different from what has been published in scientific journals [12,17].…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies [17,28,29] have found some different risk factors for SWI, identifying age, COPD and reoperation as markers. These differences may be attributed to population differences.…”
Section: Duringmentioning
confidence: 99%
“…In a study performed with 7602 patients who had undergone coronary bypass surgery, deep sternal wound infection, and mortality rates were found to be 0.59%, and 9.1%, respectively. 2) In various studies, mortality rates associated with mediastinitis have ranged between 10% and 47%. 3) Advanced age, male gender, NYHA (New York Heart Association) class ≥3, left main coronary stenosis, bilateral internal mammary artery harvesting, body mass index over 30 kg/m 2 , chronic obstructive pulmonary disease, smoking, diabetes mellitus, prolonged mechanical ventilation, re-exploration due to bleeding and massive blood transfusion are found to be the independent risk factors for mediastinitis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also pointed out that bone wax has an alleviating effect on infections and wound healing inhibitors. 2) In the present study, we aimed to investigate abovementioned effects of bone wax.…”
mentioning
confidence: 99%
“…The Fowler model also provides for inclusion of important intraoperative details known to influence postoperative infection including the need for intra-aortic balloon counterpulsation and prolonged cardiopulmonary bypass times [13]. Although the model devised by Fowler et al was based on various cases of major infection after coronary artery surgery, including DSWI, the authors did validate the model as predictive of infection in a test population from the STS Database, and the model was also recently validated in a different cohort of patients from the UK as being predictive of DSWI [38]. The EuroSCORE system also has been shown to predict infection and associated mortality with acceptable discrimination [39].…”
Section: Risk Factors and Pathophysiologymentioning
confidence: 99%